On the origins of the semen analysis: A close relationship with the history of the reproductive medicine - Fernando Tadeu Andrade-Rocha (Wolters Kluwer Medknow Publications, 2017)
The spermatozoa were first seen in ejaculates in the 17th century. However, the basic mechanisms of human fertilization have been only fully understood after the discovery of ovum in 1827. As a result, the interest in developing technologies for semen analysis arose from the early 1900s. Indeed, standard methodologies for semen analysis were designed mostly along the first half of the 20th century. Before the 1930s, semen analysis was nearly unavailable clinically, since there were still no robust methodologies for assessing sperm characteristics, as well as to set up standard references that could be able to assess the reproductive capacity of men. However, joining some methodologies reported from 1910 up to 1930, standardization was attained and thereby semen analysis increasingly assumed its role in laboratory practice for investigating men in barren marriage. This article aims in reviewing historical backgrounds on the semen analysis, up to its insertion in laboratory practice. Emphasis is given to the major studies that contributed either directly or indirectly in developing the earliest routine for the semen analysis.